N-Hydroxy-N-Propargylamide Derivatives of Ferulic Acid: Inhibitors of Cholinesterases and Monoamine Oxidases - Óscar M. Bautista-Aguilera; José M. Alonso; Marco Catto; Isabel Iriepa; Damijan Knez; Stanislav Gobec; José Marco-Contelles (Molecules, 2022)
Alzheimer’s disease (AD) is a complex disorder characterized by impaired neurotransmission in cholinergic and monoaminergic neurons, which, in combination with the accumulation of misfolded proteins and increased oxidative stress, leads to the typical features of the disease at the biomolecular level. Given the limited therapeutic success of approved drugs, it is imperative to explore rationally supported therapeutic approaches to combat this disease. The search for novel scaffolds that bind to different receptors and inhibit AD disease-related enzymes could lead to new therapeutic solutions. Here, we describe N-hydroxy-N-propargylamide hybrids 1–6, which were designed by combining the structures of Contilisant—a multifunctional anti-AD ligand—and ferulic acid, a natural antioxidant with various other biological activities. Among the synthesized compounds, we identified compound 4 as a micromolar inhibitor of hAChE with a potent radical-scavenging capacity comparable to resveratrol and Trolox. In addition, compound 4 chelated copper(II) ions associated with amyloid β pathology, mitochondrial dysfunction, and oxidative stress. The promising in vitro activity combined with favorable drug-like properties and predicted blood-brain barrier permeability make compound 4 a multifunctional ligand that merits further studies at the biochemical and cellular levels.